Factors Affecting Intention to Adopt Digital Currency among Digital Payment Users in Kathmandu Valley - Dhami, Dipesh; Thakur, Ritesh Kumar; Tamang, Akash (SAIM Journal of Social Science and Technology, 2024)
Purpose: The purpose of this paper is to investigate the factors affecting behavioral intention (INT) for adopting digital currency among digital payment users in Kathmandu Valley. Design/Methodology/Approach: This paper applied a cross-sectional survey design and collected 291 data from digital payment users in Kathmandu Valley analyzed by partial least squares structural equation model (PLS-SEM). Findings: This paper highlights that attitude (ATT) and perceived behavioral control (PBC) for adopting digital currency are the major factors that influence INT for adopting digital currency. Likewise, peer influence (PI) and superior influence (SI) have a significant positive influence on subjective norms (SN). Further, perceived ease of use (PEOU), perceived usefulness (PU), and perceived trust (PT) have a significant positive influence on ATT for adopting digital currency. Furthermore, self-efficacy (SE) and facilitating conditions (FC) have a significant positive influence on PBC. Originality/Value: The policymakers can utilize this information to develop infrastructure and regulations that encourage the use of digital currencies.